(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1913)
The document is a Privilegium or Charter of Confirmation of its privileges granted in the year 1219 by Pope Honorius III to the Cistercian Abbey of Kinloss, in Morayshire. A large part of the charter recites the privileges usually accorded to foundations of the Cistercian order. A transcript of the charter in Latin is included.